THE INFLUENCE OF LOCAL WISDOM “RAMBU SOLO”, CULTURAL IDENTITY, AND POWER DISTANCE ON THE LEADERSHIP STYLE OF THE HEAD OF LEMBANG BUNTU DATU, MENGKENDEK SUBDISTRICT, TANA TORAJA - Rasnawati Rasnawati; Andi Jam’an; Muchriana Muchran (Prodi Ilmu Pemerintahan, Universitas AMIKOM Yogyakarta, 2026)
This study aims to analyze the influence of local wisdom Rambu Solo’, cultural identity, and power distance on the leadership style of the Head of Lembang in Lembang Buntu Datu, Tana Toraja. The problem discussed in this study is the tension between efforts to implement a participatory-modern leadership style and the strong influence of the hierarchical social structure rooted in Lembang Buntu Datu. The study uses a quantitative approach with an explanatory research design involving 85 respondents through purposive sampling. Data were analyzed using multiple linear regression with the help of SPSS. The results showed that Rambu Solo’ had a positive and significant effect (p = 0.009 < 0.05) and power distance had a significant positive effect (p = 0.004 < 0.05) on leadership style. However, cultural identity did not have a significant effect (p = 0.195 > 0.05). The regression model was declared feasible through the F-test, with a coefficient of determination (R^2) of 25.6%. Meanwhile, 74.4% ois a variation that cannot be explained by this research model. This study provides a theoretical contribution to the development of culture-based leadership by integrating local wisdom and power distance dimensions.